2021
DOI: 10.3389/fmed.2021.795595
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Timing of Postoperative Weight-Bearing on Implant Failure Rate Among Older Patients With Intertrochanteric Hip Fractures: A Propensity Score Matching Cohort Study

Abstract: Introduction: The purpose of this study was to determine whether immediate weight-bearing as tolerated increased the risk of implant failure and decreased functional outcomes compared with restricted weight-bearing.Methods: From January 2010 to December 2018, 1,125 consecutive patients (≥65 years) with intertrochanteric fractures were identified. Of them, 130 patients were excluded, resulting in 995 patients in final cohort (563 receiving immediate weight-bearing and 432 receiving restricted weight-bearing). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[6][7][8][9] In previous reports, the disadvantages of WB restriction included delayed recovery of walking ability and rehabilitation after surgery. 14,20 Jia X, et al reported a significantly longer time to full WB application in the group with WB restriction. 14 Postoperative WB restriction is also associated with increased medical complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] In previous reports, the disadvantages of WB restriction included delayed recovery of walking ability and rehabilitation after surgery. 14,20 Jia X, et al reported a significantly longer time to full WB application in the group with WB restriction. 14 Postoperative WB restriction is also associated with increased medical complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…14,20 Jia X, et al reported a significantly longer time to full WB application in the group with WB restriction. 14 Postoperative WB restriction is also associated with increased medical complications and mortality. 13,19 In our study, there were no significant differences in medical complications, changes in walking ability, or length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the rehabilitation period, weight-bearing by a fractured limb and transferring it to the healthy side are critical requirements to encounter [5,7]. A gait cycle (GC) presents a period from one heel contact to the next heel contact of the same limb [8].…”
mentioning
confidence: 99%